In defense of sharks moral issues in hostile liquidating takeovers - Almeder, Robert F. (Journal of business ethics, 1991)
In this essay we defend the view that from a purely rule-utilitarian perspective there is no sound argument favoring the immorality of hostile liquidating buyouts. All arguments favoring such a view are seriously flawed. Moreover, there are some good argument favoring the view that such buyouts may be morally obligatory from the rule-utilitarian perspective. We also defend the view that most of the “shark repellents” in the market are immoral. If we are right in our arguments there is no justification, moral or otherwise, for any form of legislation that would constrain the practice of hostile liquidating buyouts.